Increased Thrombogenic Potential of Human Monocyte-derived Macrophages Spontaneously Transformed into Foam Cells - Colli, Susanna; Lalli, Mariagrazia; Risè, Patrizia; Mussoni, Luciana; Eligini, Sonia; Galli, Claudio; Tremoli, Elena (Thrombosis and Haemostasis, 1999)
This study investigated whether spontaneous lipid enrichment of human macrophages affects their thrombogenic potential as measured by increased production of tissue factor (TF) and plasminogen activation inhibitor types 1 and 2 (PAI-1 and PAI-2). Macrophages were obtained following a 7-day culture period of monocytes, isolated from the same donor, in autologous serum (HS) or in fetal bovine serum (FBS). Those cultured in HS underwent marked lipid accumulation relative to those cultured in FBS that was accompanied by increased production of TF and PAI-1, but not of PAI-2, and decreased production of interleukin-1β. They also contained more arachidonic and linoleic acid and lower amounts of n-3 polyunsaturated fatty acids, particularly docosahexaenoic acid (22:6). These data indicate that the transformation of macrophages into foam cells results in an increase in their thrombogenic and antifibrinolytic potential and provide a possible explanation of the thrombotic sequelae frequently consequent on plaque fissuring and disruption.